2011
DOI: 10.1371/journal.pone.0028844
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessel Invasion as a Strong Independent Prognostic Indicator in Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: Background and ObjectiveBlood vessel invasion plays a very important role in the progression and metastasis of cancer. However, blood vessel invasion as a prognostic factor for survival in non-small cell lung cancer (NSCLC) remains controversial. The aim of this study is to explore the relationship between blood vessel invasion and outcome in patients with NSCLC using meta-analysis.MethodsA meta-analysis of published studies was conducted to investigate the effects of blood vessel invasion on both relapse-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 73 publications
1
32
1
4
Order By: Relevance
“…The presence of vascular invasion by neoplastic cells indicates that the cancers are in a metastatic phase. Our previous meta-analysis found that LVI is a prognostic factor for survival in patients with NSCLC [8]. In the present study, we obtained summary statistics indicating that LVI status predicts poor survival in patients with NSCLC regardless of tumor size or lymph node status according to univariate or multivariate analysis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The presence of vascular invasion by neoplastic cells indicates that the cancers are in a metastatic phase. Our previous meta-analysis found that LVI is a prognostic factor for survival in patients with NSCLC [8]. In the present study, we obtained summary statistics indicating that LVI status predicts poor survival in patients with NSCLC regardless of tumor size or lymph node status according to univariate or multivariate analysis.…”
Section: Discussionmentioning
confidence: 60%
“…Blood vessel invasion (BVI) also exerts an important influence on patient outcome. The relative risk of recurrence and death for an individual patient whose tumor showed BVI by tumor cells was nearly 4 and 2 times higher, respectively, than that of a patient whose tumor did not show BVI by tumor cells [8].…”
Section: Introductionmentioning
confidence: 82%
“…Haemoglobin level (,12 g?dL -1 ) might be associated with a higher mortality and preoperative high Cyfra 21-1 level has been associated with higher risk of relapse [14]. Blood vessel invasion is associated to an increased risk of relapse and death as shown by a meta-analysis (multivariate combined hazard ratio for relapse free survival 3.98 (95% CI 2.24-7.06) and for survival 1.90 (95% CI 1.65-2.19)) [15].…”
Section: Classical Host-related and Tumour-related Factorsmentioning
confidence: 96%
“…In fact, studies have shown that good clinical outcomes are limited to lung cancer patients who are diagnosed before blood vessel invasion and before the disease metastasizes to the regional lymph nodes or has locally advanced (3,4). For this reason, much effort has focused on improving the rates of early diagnosis through improved imaging technology and adaption of screening programs.…”
Section: Introductionmentioning
confidence: 99%